PERSEPSI PETANI TERHADAP KEBERLANJUTAN LAHAN PERTANIAN DI PINGGIRAN KOTA PEKALONGAN, PROVINSI JAWA TENGAH - Imade Yoga Prasada (Journal of Data Science Theory and Application, 2023)
The conversion of agricultural land to urban areas encourages the phenomenon of urban sprawl. The urban sprawl phenomenon threatens the sustainability of agricultural land in suburban areas. On the other hand, the existence of agricultural land has an important role, both as supporting the availability of food for the population, and various other ecological roles. Therefore, this research was conducted with the aim of determining the level of farmers' perception of the sustainability of agricultural land on the outskirts of Pekalongan City in terms of five dimensions of sustainability. The research was conducted on the outskirts of Pekalongan City, Central Java Province. The number of research respondents was 90 farmers who were divided proportionally in each sub-district. Data were analyzed using a Likert scale and tested using the proportion test. The results of the research show that four of the five sustainability dimensions of farmers have a poor level of perception, and the other sustainability dimension of farmers has a good level of perception. However, if viewed based on the five dimensions simultaneously, more than 50% of farmers have a bad perception of the sustainability of agricultural land on the outskirts of Pekalongan City.